Community Social Work in Ukraine: towards the Development of New Practice Models - Slozanska, Hanna Ivanivna; Horishna, Nadia; Romanovska, Lyudmila (Socialinė teorija, empirija, politika ir praktika, 2020)
The reorganization of social welfare due to the decentralization reform implemented in Ukraine calls for the development and implementation of new practice models of service delivery best suited for community social work. The research is dedicated to discussion of the development of new models of community social work from a Ukrainian perspective, taking into consideration the community social work and community social service delivery concepts given in the literature and community-based practice models implemented abroad. The article reviews the major competencies social workers need to provide services within the local communities. Implications for future research in the field of community social work are addressed in the concluding part of the paper.
Keywords: community social work; community practice; community social service delivery; community social work practice models; amalgamated territorial communities; Ukraine